Association between monocyte to HDL cholesterol ratio and mitral annulus calcification - Erken Pamukcu, Hilal; Aker, Mert (Journal of Surgery and Medicine, 2019)
Aim: Mitral annulus calcification (MAC) is characterized by degenerative calcification of the mitral valve annulus, MAC and atherosclerosis are similar in regard to risk factors and pathogenesis. Monocyte count to high density lipoprotein (HDL) cholesterol ratio (MHR) is an inflammatory marker that is associated with several atherosclerotic diseases. We aimed to show the association of MHR levels with the presence of MAC. Methods: This retrospective cohort study was conducted with MAC (+) patients who admitted to our echocardiography laboratory which constituted the study group (n=200) and MAC (-) patients which constituted the control group. Demographic features like age and sex, presence of hypertension and diabetes mellitus were similar between groups. Laboratory and echocardiographic parameters were recorded and evaluated for statistical analysis. Results: When groups were compared according to echocardiographic parameters; left atrial diameter, pulmonary artery systolic pressure (PASP) were found to be positively correlated with the presence of MAC (r=0.271, p<0.001; r=0.329, p<0.001, respectively). MHR was significantly higher in study group {15.3 (11.9-20.6) vs. 10.8 (8.6-16.9) p<0.001}. In correlation analysis, MHR value was found to be positively correlated with presence of MAC (r=0.273; p <0.001). Conclusion: We found that the presence of MAC was associated with higher MHR, and MHR was significantly correlated with MAC.